Institutional Capacity Assessment for community rangeland management institutions in Chuine conservancy, Baringo County, Kenya - Akivaga, Allan (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The ICAT assessment process involves several steps to evaluate the governance status of RMIs and facilitate subsequent improvements. Initially, the ICAT assessment serves as a monitoring tool, typically administered externally by a participatory rangeland management (PRM) facilitator. This assessment is conducted through focus group discussions involving diverse community members, including those involved in the RMIs. The Baringo County assessment was conducted on 15 February 2024 at the Sandai chief’s office. Data was collected through focus group discussions comprising 17 men and five women using the ICAT (available at https://cgspace. cgiar.org/handle/10568/128048). As noted earlier, this tool evaluates various parameters of RMIs such as governance, engagement, planning, implementation, financial competency, and monitoring. These parameters are categorized into different levels: Latent (level 1), Emerging (level 2), Established (level 3), and Advanced (level 4).